Kilowatt‐level power amplifier in a single‐ended architecture at 352 MHz. Issue 18 (1st September 2016) - Haapala, L.; Eriksson, A.; Hoang Duc, L.; Dancila, D.
Abstract : The feasibility and very good performance of a kilowatt‐level power amplifier in a single‐ended architecture, intended for energy systems are demonstrated. The prototype is designed at 352 MHz for the ESS LINAC and delivers 1250 W with 71% efficiency in pulsed operation with a duty cycle of 5%, 3.5 ms pulse at 14 Hz repetition.